2007
DOI: 10.1007/1-4020-5721-0_16
|View full text |Cite
|
Sign up to set email alerts
|

A New High Frequency Ultrasound Skin Imaging System: Imaging Properties and Clinical in Vivo Results

Abstract: Abstract:In this paper, a new high frequency ultrasound (HFUS) system for high resolution skin imaging is presented. For imaging, mechanical scans are performed with spherically focused single element transducers. Two separate applicators with different transducers are utilized to fulfill the different requirements for imaging the skin with 20 MHz ultrasound and for lower range high resolution imaging of the uppermost skin layers with HFUS in the 100 MHz range. Clinical images were acquired in the imaging lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The resolution of ultrasound increases with increasing frequency but results in decreased tissue penetration depth. Studies using 15–20 MHz ultrasound frequencies have shown a lateral resolution of 200–300 μm . Even at this level of resolution, ultrasound images still show limitation identifying pathologic processes that require visualization of very small structures as would be required for micronodular or infiltrative basal cell carcinomas (BCCs).…”
Section: Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…The resolution of ultrasound increases with increasing frequency but results in decreased tissue penetration depth. Studies using 15–20 MHz ultrasound frequencies have shown a lateral resolution of 200–300 μm . Even at this level of resolution, ultrasound images still show limitation identifying pathologic processes that require visualization of very small structures as would be required for micronodular or infiltrative basal cell carcinomas (BCCs).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Conventional ultrasound has been used to characterize various benign and malignant skin lesions in academic settings …”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…HR-US imaging HR-US imaging (39) was performed with the Collagenoson s High Resolution Ultrasound System (Minhorst GmbH & Co), a computer-supported diagnostic instrument. The broad-banded frequency spectrum ranges from 10 to 28 MHz, with a center (nominal) frequency of 22 MHz, alternatively providing an A, B or TM image.…”
Section: Thiersch Autograftmentioning
confidence: 99%
“…7,8 High-frequency ultrasound (HFUS) imaging (>30 MHz) has been used widely in many preclinical and clinical applications. [9][10][11] The major advantage of HFUS is its high spatial image resolution; however, the large attenuation makes it suitable for imaging superficial tissue such as the eye 12,13 or skin, 14,15 intravascular ultrasound, 16,17 and small animal imaging. 18,19 Two types of HFUS systems, single element (for mechanical scanning) and array (for electronic scanning) transducers, are available for M-mode, B-mode, and Doppler mode imaging [including pulsed-wave Doppler sonography, power Doppler imaging, and color Doppler imaging (CDI)].…”
Section: Introductionmentioning
confidence: 99%